High school musical [videorecording (DVD)]. - Ortega, Kenny; Efron, Zac; Hudgens, Vanessa, 1988-; Tisdale, Ashley, 1985- (Disney, 2006)
A popular high school basketball star and a shy, academically gifted newcomer secretly decide to audition for their school's musical, a decision that turns their world and their school upside down. Includes original and sing-along versions.